A novel variant of IHH in a Chinese family with brachydactyly type 1 - Qi Yang; Jin Wang; Xiaoxian Tian; Fei Shen; Jing Lan; Qiang Zhang; Xin Fan; Shang Yi; Mengting Li; Yiping Shen (BMC Medical Genetics, 2020)
Abstract Background Brachydactyly type A1(BDA-1) is an autosomal dominant disorder which is caused by heterozygous pathogenic variants in a specific region of the N-terminal active fragment of Indian Hedgehog (IHH). The disorder is mainly characterized by shortening or missing of the middle phalanges. In this study, Our purpose is to identify the pathogenic variations associated with BDA-1 involved in a five-generation Chinese family. Methods A BDA-1 family with 8 affected and 14 unaffected family members was recruited. Whole exome sequencing (WES) was performed to identify the pathogenic variant in the proband, and which was later confirmed and segregated by Sanger sequencing. The significance of variants were assessed using several molecular and bioinformatics analysis methods. Results We uncovered a novel heterozygous missense variant c.299A > G (p.D100G) at the mutational hotspot of IHH gene following whole-exome sequencing of a Chinese family with BDA-1. The variant co-segregated with BDA-1 in the pedigree, showed 100% penetrance for phalange phenotype with variable expressivity. Conclusions In conclusion, this study reports a five-generation Chinese family with BDA-1 due to a novel pathogenic variant (c.299A > G (p.D100G)) of IHH and expands the clinical and genetic spectrum of BDA-1.